COMO PROFISSIONAIS DA EQUIPE MULTIDISCIPLINAR PODEM HUMANIZAR O CUIDADO PALIATIVO EM PACIENTES ONCOLÓGICOS: HOW PROFESSIONALS OF THE MULTIDISCIPLINARY TEAM CAN HMANIZE PALLIATIVE CARE FOR ONCOLOGY PATIENTS (REMUNOM, 2025)
AbstractPalliative care in oncology plays a crucial role in improving the quality of life of patients with advanced chronic diseases. This study explores how a multidisciplinary team can humanize palliative care, focusing on aspects such as empathetic communication, interdisciplinarity, family support, spirituality, and technology use. Based on a qualitative methodology through a literature review, the findings highlight the importance of continued professional training and public policies integrating these practices into the Brazilian Unified Health System (SUS). The results underscore the need for structural improvements to reduce regional disparities and enhance healthcare outcomes, emphasizing that humanized care significantly impacts patients' and families' well-being. Keywords: palliative care; oncology; humanization; multidisciplinary team; Unified Health System (SUS).